2020
DOI: 10.1177/1536012120968669
|View full text |Cite
|
Sign up to set email alerts
|

[11C]Methionine and [11C]PBR28 as PET Imaging Tracers to Differentiate Metastatic Tumor Recurrence or Radiation Necrosis

Abstract: Purpose: As stereotactic radiosurgery (SRS) and immunotherapy are increasingly used to treat brain metastases, incidence of radiation necrosis (RN) is consequently rising. Differentiating tumor regrowth (TR) from RN is vital in management but difficult to assess using MRI. We hypothesized that tumor methionine levels would be elevated given increased metabolism and high amino acid uptake, whereas RN would increase inflammation marked by upregulated translocator protein (PBR-TSPO), which can be quantified with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These results highlighted the heterogeneity of the immune tumour microenvironment on one hand, and on the other hand, the fact that neuroinflammation may not overlap with tumour proliferation. As another example of this caveat, neuroinflammation in the context of brain metastases was recently reported in 5 cases of non-small cells lung carcinoma and melanoma brain metastases [ 191 ], but [ 11 C]PBR28, in contrast to [ 11 C]methionine, could not differentiate metastatic tumour recurrence from neuroinflammation-induced radiation necrosis.…”
Section: Discussion On Each Group Of Diseasementioning
confidence: 99%
“…These results highlighted the heterogeneity of the immune tumour microenvironment on one hand, and on the other hand, the fact that neuroinflammation may not overlap with tumour proliferation. As another example of this caveat, neuroinflammation in the context of brain metastases was recently reported in 5 cases of non-small cells lung carcinoma and melanoma brain metastases [ 191 ], but [ 11 C]PBR28, in contrast to [ 11 C]methionine, could not differentiate metastatic tumour recurrence from neuroinflammation-induced radiation necrosis.…”
Section: Discussion On Each Group Of Diseasementioning
confidence: 99%
“…Thus, the use of the [ 11 C]methionine and [ 11 C]PBR28 tracers in PET was evaluated in 5 patients previously treated brain metastases showing regrowth. The use of [ 11 C]methionine could accurately identify pathologically confirmed tumor regrowth in all 7 lesions examined, whereas [ 11 C]PBR28 could only identify 3 of 7 lesions, indicating that the former, but not the later tracer can be used as a reliable marker [84].…”
Section: Brain Metastases Inflammation and Imagingmentioning
confidence: 97%
“…A head-to-head comparison study conducted by Tomura et al found that 11C-MET PET was better than FDG PET in distinguishing radiation necrosis from recurrent metastatic disease in the brain (38,40). Another recent study by Tran et al found that 11C-MET was a reliable marker for detecting recurrent disease in the post radiation setting; for example, 11C-MET was able to correctly identify pathologically confirmed recurrent disease in 7 lesions in 5 patients (41,42).…”
Section: Amino Acidsmentioning
confidence: 99%